The incidence of CO₂ emissions pricing under alternative international market responses: A computable general equilibrium analysis for Germany - Christoph Böhringer; Thomas F. Rutherford; Jan Schneider (University of Oldenburg, Department of Economics, 2021)
We investigate the economic impacts of CO2 emissions pricing for Germany in the context of the Paris Agreement where we highlight the role of international market responses for the incidence across heterogeneous households. We consider three settings for international spillover effects: (i) a small-open-economy framework where international commodity prices remain constant, (ii) a multi-region-trade framework with endogenous terms of trade where only Germany undertakes emission pricing, and (iii) a multi-region-trade framework where all other regions also price CO2 emissions. In all three settings Germany complies to a given domestic CO2 emissions reduction target through economy-wide uniform CO2 emissions pricing. CO2 revenues are recycled lump-sum to households on an equal-per-household basis. We find that the small-openeconomy setting in the case of Germany not only overstates overall economic adjustment costs to CO2 emissions pricing, but also understates the degree of progressiveness of CO2 revenue recycling. The reason is that in the multi-region-trade frameworks Germany is able to pass through part of its economic adjustment costs to trading partners via higher export prices. As a consequence, the CO2 prices required to achieve the domestic emissions reduction target are higher, yielding more CO2 revenues that are recycled to households.
Keywords: D58; H22; H23; Q58; 330; computable general equilibrium; incidence; environmental taxes